AUGMENTED REALITY APPLICATIONS FOR TRANSFORMING PUBLIC ART INSTALLATIONS INTO IMMERSIVE EXPERIENCES - Sule, Bipin; Bhan, Suraj; Gawhale, Swati Gopal; Bainalwar, Prachi Dussawar; Li, Wei; Sundareswaran, Deepa (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Public art installation is influential in cultural identity of the urban areas and community interaction. Nonetheless, conventional art objects in the community tend to be confined to two-dimensional visual experiences, which limits the variety of the experiences and interpretations of the viewers. The new possibilities which are offered by the recent developments in Augmented Reality (AR) technologies allow changing the traditional public art into an interactive and immersive cultural experience. This paper proposes the exploration of integrating AR technologies to physical installations of public art to improve participation, storytelling, and learning. The given structure integrates both physical artworks and digital AR overlays and allows users to view dynamic multimedia content like animations, historical stories, and interactive visualization on mobile devices or AR headsets. The study describes a conceptual design comprising of hardware units, AR software solutions, computer vision algorithms and spatial computing technologies of location-based interaction. Also, the principles of interaction design are addressed to create more engaging interfaces through the effort of determination of intuitive gesture and touch interfaces. A prototype AR public art system is tested in terms of user experience characteristics such as duration of engagement, frequency of interaction, and immersion.